2008
DOI: 10.1074/jbc.m709857200
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Factor 5 Causes Cartilage Degradation through Transactivation of Matrix Metalloproteinase 9

Abstract: Although degradation of cartilage matrix has been suggested to be a rate-limiting step for endochondral ossification during skeletal development, little is known about the transcriptional regulation. This study investigated the involvement of KLF5 (Krüppel-like factor 5), an Sp/KLF family member, in the skeletal development. KLF5 was expressed in chondrocytes and osteoblasts but not in osteoclasts. The heterozygous deficient (KLF5 ؉/؊ ) mice exhibited skeletal growth retardation in the perinatal period. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…5B). Hypertrophic chondrocytes also promote the destruction of growth plate cartilage by expression of a number of catabolic enzymes, including the matrix metalloproteinases (MMPs) MMP13 (Johansson et al, 1997) and MMP9 (Shinoda et al, 2008;Golovchenko et al, 2013) and the aggrecanases ADAMTS4 and ADAMTS5 (Glasson et al, 2004;Rogerson et al, 2008). We reasoned that, since ephrin B2 deletion was targeted to osteoblasts and chondrocytes, the lack of cartilage destruction in Osx1Cre.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B). Hypertrophic chondrocytes also promote the destruction of growth plate cartilage by expression of a number of catabolic enzymes, including the matrix metalloproteinases (MMPs) MMP13 (Johansson et al, 1997) and MMP9 (Shinoda et al, 2008;Golovchenko et al, 2013) and the aggrecanases ADAMTS4 and ADAMTS5 (Glasson et al, 2004;Rogerson et al, 2008). We reasoned that, since ephrin B2 deletion was targeted to osteoblasts and chondrocytes, the lack of cartilage destruction in Osx1Cre.…”
Section: Resultsmentioning
confidence: 99%
“…Hypertrophic chondrocytes also express metalloproteinases and aggrecanases (Johansson et al, 1997;Glasson et al, 2004;Shinoda et al, 2008;Golovchenko et al, 2013) and there are several lines of evidence indicating that these regulate osteoclast activity during endochondral ossification. Mice carrying a collagen mutation rendering it resistant to collagenases show impaired osteoclastic resorption of growth plate cartilage (Chiusaroli et al, 2003), while Mmp13 null mice show impaired osteoclast attachment in endochondral fracture healing (Holliday et al, 1997;Kosaki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…KLF5 is a transcription factor, so we predicted that EMT induced by KLF5 knockdown is mediated by key transcriptional targets of KLF5. Several microarray-based studies have identified a large number of protein-coding genes that are transcriptionally regulated by KLF5 (3,(50)(51)(52). Evaluation of these KLF5 target genes did not point to significant regulators of EMT.…”
Section: Klf5 Is Significantly Downregulated During the Emt Process Imentioning
confidence: 99%
“…Scale bar: 0.2 amino acid changes per site. (Frontelo et al, 2007;Nuez et al, 1995;Ouyang et al, 1998;Perkins et al, 1995;Siatecka et al, 2007;Zhang et al, 2001b) (Anderson et al, 1995;Basu et al, 2005;Carlson et al, 2006;Kuo et al, 1997a;Kuo et al, 1997b;Lee et al, 2006;Nakagawa et al, 2008;Wang et al, 2013;Wani et al, 1999a,b;Wu et al, 2005;Xie et al, 2011;Zhang et al, 2004 (Chaib et al, 2001;Chen et al, 2002;Chen et al, 2005a;Conkright et al, 1999;Du et al, 2007;Ge et al, 2015;He et al, 2009;Liu et al, 2010;McConnell et al, 2009;McConnell et al, 2007;Nakagawa et al, 2008;Nandan et al, 2010;Nandan et al, 2008;Oishi et al, 2008;Oishi et al, 2005;Qin et al, 2015;Shindo et al, 2002;Shinoda et al, 2008;Takeda et al, 2010;Tong et al, 2006;Wan et al, 2008;...…”
Section: Other Endoderm-derived Organsmentioning
confidence: 99%